2016
DOI: 10.2147/ijn.s110465
|View full text |Cite
|
Sign up to set email alerts
|

Metal oxide nanoparticles interact with immune cells and activate different cellular responses

Abstract: Besides cell death, nanoparticles (Nps) can induce other cellular responses such as inflammation. The potential immune response mediated by the exposure of human lymphoid cells to metal oxide Nps (moNps) was characterized using four different moNps (CeO 2 , TiO 2 , Al 2 O 3 , and ZnO) to study the three most relevant mitogen-activated protein kinase subfamilies and the nuclear factor kappa-light-chain-enhancer of the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…Cultured cells were exposed to different concentrations of APS-MNPs (ranging from 10 to 500 µg Fe/ml) for 24 h. At all tested concentrations viability was over 100% compared to untreated cells maintained at standard culture conditions, although no statistically significant differences were found. This result suggests a slight induction of T cell proliferation by MNPs, as described for other metal oxide nanoparticles 65 . .…”
Section: Influence Of Subcellular Localization On Mhtsupporting
confidence: 67%
“…Cultured cells were exposed to different concentrations of APS-MNPs (ranging from 10 to 500 µg Fe/ml) for 24 h. At all tested concentrations viability was over 100% compared to untreated cells maintained at standard culture conditions, although no statistically significant differences were found. This result suggests a slight induction of T cell proliferation by MNPs, as described for other metal oxide nanoparticles 65 . .…”
Section: Influence Of Subcellular Localization On Mhtsupporting
confidence: 67%
“…Nevertheless, other studies have shown that MNPs can induce some intracellular activation markers in certain cases [61,62], although this depends mainly on NP design [63].…”
Section: Dicussionmentioning
confidence: 92%
“…Preliminary tests conducted in our laboratory on Jurkat cells proved that ZnO (50 and 100 µg/mL) causes the activation of three mitogen-activated protein kinases (MAPKs), thus inducing the phosphorylation of p38, ERK 1/2 and SAPK/JNK, together with the degradation of IκBα, the NFκB inhibitor. In contrast, Al 2 O 3 , CeO 2 and TiO 2 only showed activation of some of these routes and the degradation of IκBα at high concentrations (100 µg/mL) [ 24 ]. Moreover, Jurkat cells were more sensitive to activation of these signalling proteins when compared to NCI-H460 cells [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Jurkat cells, where only ERK1/2 and p38 were activated by CeO 2 Nps mainly after pre-stimulation of the cells, in human hepatoma cells the SAPK/JNK was also activated by these Nps and activation of the three MAPKs was associated with oxidative stress and reduced cell viability at concentrations ≥50 µg/mL [ 27 ]. Interestingly, TiO 2 Nps induced activation of ERK1/2 and p38 in a human neutrophil [ 29 ] and a bronchial epithelial cell line [ 30 ] as described for Jurkat cells [ 24 ]. However, the activation of these signalling proteins was associated with the inhibition of apoptosis in the lymphocytic and neutrophil cell line, while in the bronchial epithelial cells the Nps induced apoptosis and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%